Overcoming Challenges through Product Innovation and Entrepreneurial Spirit during VUCA World - Allicia Deana Santosa (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2023)
The global spread of COVID-19, evolving government regulations, diverse external circumstances, and worldwide events such as conflicts or wars have placed businesses in unprecedented volatility, uncertainty, complexity, and ambiguity (VUCA). This situation undeniably exerts a significant influence on Micro, Small, and Medium Enterprises (MSMEs), including local coffee shops. The escalating competition within the industry and the challenges posed by the VUCA environment compel coffee shop entrepreneurs to enhance their competitive capabilities, all while witnessing a rise in the number of local coffee shops during the pandemic. The primary objective of this research was to investigate how entrepreneurial spirit and product innovation impact business performance amid the VUCA environment. The research method used in this study is quantitative methods. The study involved a sample of 51 coffee shop entrepreneurs located in Tasikmalaya and Ciamis as participants. The findings of this research reveal that both entrepreneurial spirit and product innovation have a positive influence on business performance and facilitate businesses in adapting to the challenges posed by the VUCA environment.